Very late-onset neuromyelitis optica spectrum disorder beyond the age of 75 - Krumbholz, Markus; Hofstadt-van Oy, Ulrich; Angstwurm, Klemens; Kleiter, Ingo; Jarius, Sven; Paul, Friedemann; Aktas, Orhan; Buchholz, Grete; Kern, Peter; Straube, Andreas; Kümpfel, Tania (Journal of neurology, 2015)
Aquaporin-4 antibody (AQP4-Ab)-positive neuromyelitis optica spectrum disorder (NMOSD) is a rare but often severe autoimmune disease with median onset around 40 years of age. We report characteristics of three very-late-onset NMOSD (including complete NMO) patients >75 years of age, in whom this diagnosis initially seemed unlikely because of their age and age-associated concomitant diseases, and briefly review the literature.
Gesehen am 29.05.2020